Capturing dynamics in nursing: a diary study of nurses’ job characteristics and ability and willingness to continue working - Vermeulen, Renée Cornelia Josephina Maria; van Leeuwen, Evelien Hanna (Frontiers in Psychology, 2023)
Objectives:This study aimed to gain insight into (1) the dynamics of job characteristics (demands and resources) of nurses and (2) how job characteristics relate to nurses' ability and willingness to continue working (understood as employability). Job characteristics are profession-specific and vary over time, but studies often overlook these dynamics. Moreover, job characteristics relate to nurses' employability, which is under pressure due to a rapidly changing work environment. It is necessary to gain insight into the dynamic job characteristics of nurses to develop targeted workplace interventions that help nurses remain employable.Methods:This study adopted a mixed methods diary approach, with a strong emphasis on qualitative analysis. 46 Nurses from two hospitals in a large Dutch city completed a structured diary at six points over three weeks, resulting in 225 diary entries in total. The nurses used a custom-made application on their mobile devices to describe in their own words what they experienced as demanding and resourceful throughout the shifts and how they experienced their employability. Prior to the diaries, nurses completed an intake survey.Results:A within-person analysis highlighted the day-to-day dynamics in the nursing profession. The job characteristics a nurse mentioned in the first diary entry often were completely different from the job characteristics the same nurse mentioned in the other diary entries. This analysis also showed variety within nurses' employability, demonstrating that perceptions of employability vary over time. A between-person analysis highlighted links between job characteristics and nurses' employability: social interactions strengthen a nurse's employability, a strict task approach threatens it, and aspects such as a strong drive to care, professional development, and autonomy (clustered as aspects that enable to 'act professionally') create opportunities to enhance employability.Conclusions:Insights from this study show that job characteristics typical of the nursing profession can be linked to nurses' perceptions of employability. Also, it stems from this research that not only job characteristics but also employability are dynamic in the short run. Understanding and enhancing employability in a nursing context requires capturing these dynamics, for instance by collecting data at several points in time or by using mixed-method studies to understand employability scores within their context.